2016
DOI: 10.3389/fmicb.2016.01856
|View full text |Cite
|
Sign up to set email alerts
|

Community-Metabolome Correlations of Gut Microbiota from Child-Turcotte-Pugh of A and B Patients

Abstract: The gut flora are widely involved in the cometabolism with the host and have evident effects on the metabolic phenotype of host. This study performed a metabolome analysis of the intestinal microbiota specific for liver cirrhosis. The study population included patients with Child-Turcotte-Pugh score of A (AP, n = 5) and B (BP, n = 5), and control subjects (NM, n = 3). Metagenomic DNA from fecal microbiota was extracted followed by metagenomic sequencing through Illumina MiSeq high throughput sequencing of 16S … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
15
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 14 publications
(17 citation statements)
references
References 38 publications
2
15
0
Order By: Relevance
“…Hepatic encephalopathy was regarded as a typical model of gut-liver-brain axis diseases [11]. Gut microbiota had extensive participation in human metabolism [4]. In cirrhotic patients, changes of intestinal microbial community and the metabolic byproducts, local and systemic inflammation, and intestinal barrier dysfunction will drive the development of hepatic encephalopathy [11].…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Hepatic encephalopathy was regarded as a typical model of gut-liver-brain axis diseases [11]. Gut microbiota had extensive participation in human metabolism [4]. In cirrhotic patients, changes of intestinal microbial community and the metabolic byproducts, local and systemic inflammation, and intestinal barrier dysfunction will drive the development of hepatic encephalopathy [11].…”
Section: Discussionmentioning
confidence: 99%
“…Gut microbiota is considered as an important endocrine organ, which can be adjusted or self-regulated [1]. Intestinal microbiota has intimate relationship with human disease and health, and has remarkable influence on the metabolic phenotype of host, with extensive participation in the cometabolism with host [3,4].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Another study showed similar result that Child–Pugh B patients contained a significant reduction of Bacteroidetes and increase in Firmicutes and Proteobacteria compared with the health people. While fecal microbiota component from Child–Pugh A patients had no significant difference from the health people ( Wei et al, 2016 ). These results indicated that normal gut microbiota depend on normal liver function, and improved liver function observed after splenectomy might have helped to restore gut microenvironment.…”
Section: Introductionmentioning
confidence: 97%
“…Dysbiosis in microbiota can disrupt the metabolic balance in the gastrointestinal tract ( Marcobal et al, 2013 ). Previous studies have reported that LC patients exhibit a distinct metabolic phenotype, such as disordered amino acid metabolism ( Huang et al, 2013 ; Wei et al, 2013 , 2016 ). In turn, the dysbiosis of gut microbiota may contribute to the progress of liver disease ( De Minicis et al, 2014 ; Tilg et al, 2016 ).…”
Section: Introductionmentioning
confidence: 99%